Development of Student Worksheets with the Context of Local Wisdom in Mathematics Learning - Supriadi, Pipit Pitriani; Astutik, Heny Sri; Pamungkas, Dwi (Indonesian Journal of Education and Mathematical Science, 2025)
The development of LKPD ensures that the instructional materials produced are relevant, effective, and suitable for students' learning needs in various educational contexts. This research aims to develop Student Worksheets based on Papuan local wisdom for mathematics learning at MAN Insan Cendekia Sorong. The research method used is RD with the ADDIE model approach. The study was conducted at MAN Insan Cendekia Sorong involving one educator and 30 students of grade XII IPA.The results show that LKPD based on local wisdom successfully enhances students' understanding of mathematics. Evaluation regarding practicality indicates that more than 87,5% of teachers and 91,12% of students. They find LKPD highly practical in its use. In terms of effectiveness, LKPD achieved an average level of learning completeness of 100%, with students demonstrating increased learning motivation and active participation in the learning process. From a validity perspective, LKPD is assessed to be aligned with curriculum standards and relevant to the educational needs of mathematics in Papua.